Molecular xenomonitoring as a post-MDA surveillance tool for global programme to eliminate lymphatic filariasis: Field validation in an evaluation unit in India. - Swaminathan Subramanian; Purushothaman Jambulingam; Kaliannagounder Krishnamoorthy; Neelavathi Sivagnaname; Candasamy Sadanandane; Venkatesan Vasuki; Chokkalingam Palaniswamy; Balakrishnan Vijayakumar; Adinarayanan Srividya; Hari Kishan K Raju (Public Library of Science (PLoS), 2020)
BACKGROUND:Lymphatic filariasis (LF) is targeted for elimination by the year 2020. As of 2017, 67 of the 72 endemic countries have implemented annual Mass Drug Administration (MDA) for interrupting LF transmission. Transmission Assessment Survey (TAS) is the recommended protocol to evaluate the impact of MDA and to decide when to stop MDA in an Evaluation Unit (EU, population ≤2 million). As the human infection levels go down with repeated MDA rounds, it becomes a challenge to select the appropriate survey methods to assess transmission interruption. This study validates a standard protocol for molecular xenomonitoring of infection in vectors (MX) at an EU as a complementary tool for TAS to stop MDA and its utility for post-MDA or post-validation surveillance. METHODOLOGY:The study was conducted in Cuddalore district, Tamil Nadu, India, which was found eligible for TAS after 15 annual rounds of MDA (4 with DEC alone and 11 with DEC plus albendazole). The district was divided into two EUs as per the TAS protocol and one EU was randomly selected for the study. A two-stage cluster design vector sampling, developed and validated at a sub-district level, was implemented in 30 randomly selected clusters in the EU. Female Culex quinquefasciatus were collected placing gravid traps overnight (1800-0600 hrs) inside the premises of systematically selected households. Pools of 20-25 blood-fed, semi-gravid and gravid Cx. quinquefasciatus were subjected to real-time quantitative PCR (polymerase chain reaction) assay for detecting Wuchereria bancrofti DNA. Pool infection rate (% of pools positive for W. bancrofti DNA), and the estimated prevalence of W. bancrofti DNA in mosquitoes and its 95% confidence interval were calculated. Additionally, in these 30 clusters, microfilaria (Mf) survey among individuals >5 years old was carried out. School-based TAS was conducted using Immunochromatographic Card Test (ICT) in the EU. Prepared itemized cost-menu for different cost components of MX survey and TAS were estimated and compared. RESULTS:MX survey showed that only 11 (3.1%) of the 358 pools (8850 Cx.quinquefasciatus females), collected from 30 clusters, were found positive for W. bancrofti DNA. The estimated vector infection rate was 0.13% (95% CI: 0.07-0.22%), below the provisional threshold (0.25%) for transmission interruption. Of 1578 children tested in the TAS, only four (0.25%) were positive for filarial antigenemia, and it is well below the critical cut-off (18 positives) for stopping MDA. Among 9804 persons tested in the 30 clusters, only four were found positive for Mf (0.04%; 95% CI: 0.01-0.1%). The Mf-prevalence was <1% threshold for transmission interruption in humans. The estimated costs for TAS and MX per EU were $14,104 USD and $14,259 USD respectively. CONCLUSIONS:The result of MX protocol was in good agreement with that of TAS, providing evidence to recommend MX as a complementary tool to TAS to decide on stopping MDA. MX can also be a potential surveillance tool for post-MDA and post-validation phases as it could detect sites with residual infection and risk of resurgence of transmission. MX is economically feasible as its cost is slightly higher than that of TAS.